A Comprehensive review on Limonene: A Versatile Ingredient in the Cosmetic Industry - Tafseel, Mohd.; Dutta, Disha; Aslam, Ramsha (Journal of Neonatal Surgery, 2025)
A naturally occurring monoterpene hydrocarbon that is mostly isolated from citrus fruits, limonene has drawn a lot of interest in the cosmetics industry because of its many uses. This chemical has several advantages, such as antibacterial properties, a nice scent, and possible skin benefits. Limonene is a common option for fragrances in body care products, colognes, and perfumes because of its refreshing aroma. Its zesty scent improves customers' entire sensory experience by being frequently linked to freshness and cleanliness. Limonene has antibacterial action against a variety of microorganisms in addition to its aroma qualities, which makes it a possible inclusion in skincare products to help stop the growth of germs and fungus. Apart from its antibacterial and aroma qualities, limonene has also been researched for possible skin health advantages. According to some study, limonene may have antioxidant qualities that help shield the skin from harm brought on by free radicals. Its ability to increase skin suppleness and lessen wrinkle appearance has also been studied. To completely comprehend the mechanics underlying these possible advantages, more study is necessary. Because of its flexibility, limonene is used in a variety of cosmetic items, such as body lotions, soaps, hair care products, colognes, and fragrances. It is anticipated that limonene's use in cosmetics would rise in tandem with consumer desire for sustainable and natural components. However, it's crucial to remember that limonene might irritate certain people, so its application needs to be carefully thought out, particularly in products meant for delicate skin